Komposisi Kimiawi dan Fraksinasi Protein Susu Kuda Sumba (THE CHEMICAL COMPOSITION AND PROTEIN FRACTIONATION OF SUMBA MARE’S MILK) - Detha, Annytha Ina Rohi; Sudarwanto, Mirnawati; Latif, Hadri; Datta, Frans Umbu (Jurnal Veteriner; Vol 15 No 4 (2014), 2015)
The aims of this study were to determine both chemical composition and fraction of the proteincompounds of sumba mare’s milk. Determination of the chemical compositions of sumba mare’s milk havedone by analyzing protein content using the Kjeldahl method, fat content using Gerber method, lactosecontent and the total solids content. Identification of antimicrobial compounds of whey proteins in milkusing high performance liquid chromatography (HPLC) method. The results showed that the average ofsumba mare’s milk contained protein, fat, lactose and total solids were; 1.82%, 1.67%, 6.48% and 11.37%respectively. The average value of protein and fat in sumba mare’s milk was decrease significantly at fifthmonth of lactation period. Based on identification of antimicrobial compounds using HPLC method, thereare six main peaks with different polarities and retention times. In conclusion, sumba mare’s milk havea balance composition that can be used as a source of nutritious food and the milk likely also has six mainantimicrobial compounds in its whey protein.
Keywords: sumba mare milk, milk composition, protein fractionation